Time periods of interfacial period of spring rape depending on intensification elements of growing in conditions of the Right-Bank Forest-Steppe of Ukraine - Єрмакова, Л. М.; Пророченко, Т. І. (Scientific Progress & Innovations, 2016)
We display effect of intensification elements of the cultivation on the length of the passage of spring rape interfacial periods in conditions of Right-Bank Forest-Steppe. It is noted that examined factors promoted different contribution of the passage phases of growth and development of plants rape in the experiment. According to the results of the study we found that if we put nitrogen fertilizer the growing period has increased in all versions, however, it was dependent on the type of fertilizer. In turn, the length of the growing season studied varieties and hybrids of spring rape was influenced by weather conditions and years of research. We found that optimization of state of nutrition by putting different types of nitrogen fertilizer (ammonium nitrate, ammonium sulfate, urea) provides a full realization of the potential of productivity of plants.